2001
DOI: 10.1097/00007632-200102010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy for Spinal Metastases

Abstract: A new surgical strategy for spinal metastases based on the prognostic scoring system is proposed. This strategy provides appropriate guidelines for treatment in all patients with spinal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,017
11
92

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,220 publications
(1,146 citation statements)
references
References 23 publications
26
1,017
11
92
Order By: Relevance
“…The authors of this study furthermore demonstrated median survival time after en bloc spondylectomy of more than 30 months and nearly 20% surviving more than 5 years. These findings underscore the results reported by Tomita et al who demonstrated median survival times in patients after en bloc resection of 38 months [33][34][35].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The authors of this study furthermore demonstrated median survival time after en bloc spondylectomy of more than 30 months and nearly 20% surviving more than 5 years. These findings underscore the results reported by Tomita et al who demonstrated median survival times in patients after en bloc resection of 38 months [33][34][35].…”
Section: Discussionsupporting
confidence: 88%
“…Tumors were equally distributed in the thoracic (n = 8) and lumbar (n = 7) spine. According to the surgical classification of vertebral tumors [32,34], the anatomic sites of eight tumors were considered as intra-and of seven tumors as extracompartmental. Five patients were treated with surgical treatment alone and another ten patients underwent neoadjuvant or adjuvant postoperative therapy, i.e., systemic polychemotherapy and/or radiation therapy (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations